Distinct encounter complexes of PAI‐1 with plasminogen activators and vitronectin revealed by changes in the conformation and dynamics of the reactive center loop. (2nd December 2015) - Qureshi, Tihami; Goswami, Sumit; McClintock, Carlee S.; Ramsey, Matthew T.; Peterson, Cynthia B.
Abstract: Plasminogen activator inhibitor‐1 (PAI‐1) is a biologically important serine protease inhibitor (serpin) that, when overexpressed, is associated with a high risk for cardiovascular disease and cancer metastasis. Several of its ligands, including vitronectin, tissue‐type and urokinase‐type plasminogen activator (tPA, uPA), affect the fate of PAI‐1. Here, we measured changes in the solvent accessibility and dynamics of an important unresolved functional region, the reactive center loop (RCL), upon binding of these ligands. Binding of the catalytically inactive S195A variant of tPA to the RCL causes an increase in fluorescence, indicating greater solvent protection, at its C‐terminus, while mobility along the loop remains relatively unchanged. In contrast, a fluorescence increase and large decrease in mobility at the N‐terminal RCL is observed upon binding of S195A‐uPA to PAI‐1. At a site distant from the RCL, binding of vitronectin results in a modest decrease in fluorescence at its proximal end without restricting overall loop dynamics. These results provide the new evidence for ligand effects on RCL conformation and dynamics and differences in the Michaelis complex with plasminogen activators that can be used for the development of more specific inhibitors to PAI‐1. This study is also the first to use electron paramagnetic resonance (EPR) spectroscopy to investigate PAI‐1 dynamics. Significance : Balanced blood homeostasis and controlled cell migration requires coordination between serine proteases, serpins, and cofactors. These ligands form noncovalent complexes, which influence the outcome of protease inhibition and associated physiological processes. This study reveals differences in binding via changes in solvent accessibility and dynamics within these complexes that can be exploited to develop more specific drugs in the treatment of diseases associated with unbalanced serpin activity.